Mapeamento do termo “profissionalização docente”: uma análise dos anais do Congresso Nacional de Educação (EDUCERE), 2008-2017 - Markic, Ana Angélica (2019)
The term "teacher professionalization" is relatively recent to refer to how the teacher constructs his or her profession. And even he has not explained how to explain this process, which is why the literature has made use of notions such as "professionalism", "professionalism" and "teacherality" as heuristic tools to better understand this professionalization process. In order to understand, therefore, how this relatively recent term in the discussion about teaching work is being understood in the national scientific community, it was decided to carry out a descriptive mapping of the research presented at the National Congress of Education - EDUCERE, organized by the Pontifical Catholic University of Paraná (PUCPR), since it is an event already consolidated in the educational scenario, constituted by an organized data base, with significant amount of academic productions and considerable representation of several national and international authors. This study was based on the works of authors such as Nóvoa (1992), Perrenoud (2002), Wittorski (2014a, 2014b), Alves and André (2013), Tardif (2012) among others who seek to understand how teachers build their profession. Access to educere data was provided by the electronic disclosure of the annals, which enabled the contact with the works published in the years 2008 to 2017, the focus of this investigation. The methodology used was a descriptive research, which is characterized by analyzing the productions published by the website of this congress. In order to give the data an organic form, a table was prepared with the analyzed works. The selection of the publications that would receive content analysis was done from a survey of those that contained, in the title, abstract or keywords, the term "teacher professionalization". Based on the analysis made, using Alceste software, four classes were generated, and classes 1 and 3 were analyzed because they were the closest semantically. The preliminary results showed an increase in the work concerning the subject, once the term professionalization was highlighted in the legislation. By analyzing the axes' nomenclatures, one can notice an oscillation and difficulty in maintaining them, which may have occasioned, quantitatively, reduction or increase in the works with the terms searched here. Thus, it is expected that this work will aid in the broader understanding of the terms presented here.